(untitled) (Research, Society and Development, 2022)
The process by which one plant community transforms into another is called succession, in which it triggers gradual changes both in abiotic conditions and in the plant composition and structure of the community, as well as its associated organisms.The aim of this study was to analyze the behavior of pollination syndromes along a successional chronosequence a fragment of Caatinga hyperxerophilic in the municipality of Serrita, Pernambuco, Brazil. The methodology was performed by transects demarcation subsequently prepared floristic inventory area and characterization of pollination syndromes in the process of a succession chronosequence, this being comprised of three stages (Initial, Intermediate and Late). The results showed that pollination systems in Caatinga species are similar to those found in dry and humid tropical forest communities, moreover, it was also found that although there are differences in species composition among successional stages, melittophily was prevalent in chronosequence analyzed in this study, and only the late stage differs markedly from the other two, with a higher proportion of pollinated by bees.